Diabetes among migrants in Denmark: Incidence, mortality, and prevalence based on a longitudinal register study of the entire Danish population. (December 2016) - Andersen, Gregers Stig; Kamper-Jørgensen, Zaza; Carstensen, Bendix; Norredam, Marie; Bygbjerg, Ib Christian; Jørgensen, Marit Eika
Highlights: This register based study covers the entire Danish population. Non-western migrants have a higher incidence of diabetes compared to native Danes. The standardised mortality ratio is higher among non-western migrants. Increased prevalence among non-western migrants is to some extent explained by increased incidence. Findings call for screening and prevention strategies targeted migrant populations. Abstract: Objective: Studies of diabetes in migrant populations have shown a higher prevalence compared to their respective countries of origin and to people natively born in the host country, but there is little population-based data on diabetes incidence and mortality in migrant populations. The aim of the current study was (1) to describe the incidence rates and prevalence of diabetes among first generation migrants in Denmark compared to the Danish background population, and (2) to compare standardised mortality rates (SMRs) for individuals with and without diabetes according to country of origin. Research design and methods: Information was obtained from linkage of the National Diabetes Register with mortality statistics and information from the Central Personal Register on country of origin. Age- and sex-specific estimates of prevalence, incidence rates, mortality rates and SMRs relative to the part of the population without diabetes were calculated based on follow up of the entire Danish population. Results: Compared with native born Danes, the incidence of diabetes was about 2.5 times higher among migrants from Africa, Asia, and the Middle East, and these migrant groups also showed significantly higher prevalence. The standardised mortality rates (SMR) were higher particularly above 50 years of age among most migrant groups compared with native born Danes, and with a higher annual increase. Conclusions: The highest diabetes incidence rates and prevalence estimates were observed among migrants from Africa, Asia, and the Middle East, and the annual increase in SMRs was higher in these groups compared to native born Danes.